Successful mechanical thrombectomy in a three-year-old boy with cardioembolic occlusion of both the basilar artery and the left middle cerebral artery. (November 2016) - Gerstl, Lucia; Olivieri, Martin; Heinen, Florian; Borggraefe, Ingo; Schroeder, Andreas Sebastian; Tacke, Moritz; Vill, Katharina; Dalla-Pozza, Robert; Reiter, Karl; Lutz, Juergen; Brueckmann, Hartmut; Janssen, Hendrik
Abstract: Background: Paediatric stroke is a potentially life-threatening emergency and requires immediate treatment to improve clinical outcome. In contrast to adult treatment recommendations, little is known about safety and efficacy of thrombolysis and mechanical thrombectomy in children. Case description and conclusion: We report on a three-year-old boy with a cardioembolic intracranial two-vessel occlusion and successful therapy with thrombolysis and mechanical thrombectomy. Furthermore, this case emphasizes the need of standardized protocols for acute management of paediatric stroke. Highlights: Time is brain – Paediatric stroke is an emergency and requires immediate treatment. There is a need of specialized 24/7 multidisciplinary paediatric stroke teams. Mechanical thrombectomy may be a promising option even in young children. A detailed risk-benefit analysis is mandatory for the use of endovascular treatment.